2016
DOI: 10.1590/s0102-865020160030000001
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress and renal lesion in mice with combination of high-fat diet and streptozotocin-induced diabetes

Abstract: PURPOSE:To investigate in the kidney the pathologic changes and expression of GRP78 and CHOP in the Kunming (KM) mice with combination of high-fat diet and streptozotocin-induced diabetes. METHODS:Sixty two male KM mice were randomly divided into a normal control (NC) group (n=20) and a high-fat diet (HFD) group (n=42). After a four-week dietary manipulation, the KM mice in the HFD group were injected intraperitoneally with streptozotocin to induce diabetes. After diabetic models were successfully established,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The endoplasmic reticulum (ER) plays a critical role in protein folding, lipid synthesis, and calcium storage and release (1). Acute nutrient excess or obesity leads to the development of ER stress, triggering the activation of a group of signaling pathways, termed the unfolded protein response (UPR), in the liver, kidneys (2), and other organs. Three ER-stress-activated enzymesinositol-requiring enzyme 1 (IRE1α), PKR-like ER kinase (PERK), and activating transcription factor 6 (ATF6)together maintain ER homeostasis by activating distinct branches of the UPR.…”
Section: Introductionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) plays a critical role in protein folding, lipid synthesis, and calcium storage and release (1). Acute nutrient excess or obesity leads to the development of ER stress, triggering the activation of a group of signaling pathways, termed the unfolded protein response (UPR), in the liver, kidneys (2), and other organs. Three ER-stress-activated enzymesinositol-requiring enzyme 1 (IRE1α), PKR-like ER kinase (PERK), and activating transcription factor 6 (ATF6)together maintain ER homeostasis by activating distinct branches of the UPR.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study also demonstrated a decreased expression of two chaperones, namely HSPA5 and HSPD1, in the kidneys of the HR-and SFA-fed animals, respectively. This phenomenon is difficult to explain in light of the significant induction of endoplasmic reticulum stress caused by the administration of HFDs recorded in other studies (Xie et al, 2016;Sánchez-Navarro et al, 2021).…”
Section: Stress-related Proteinsmentioning
confidence: 81%
“…GRP78 facilitates the proper folding of de novo proteins and regulates the unfolded protein response to control ERS in the ER [52]. In Kunming mice, a combination treatment of a high-fat diet with STZ was found to upregulate the expression of CHOP and GRP78 in the kidneys [53]. In our study, an increase in the expression of CHOP and GRP78 was observed in mice induced by STZ-LNAME and model HGMCs, but HJXJ treatment decreased the expression of CHOP and GRP78.…”
Section: Discussionmentioning
confidence: 99%